2019
DOI: 10.3892/etm.2019.8329
|View full text |Cite
|
Sign up to set email alerts
|

Crocin has pharmacological effects against the pathological behavior of colon cancer cells by interacting with the STAT3 signaling pathway

Abstract: The aim of the present study was to investigate changes in proliferation, apoptosis, inflammation and chemokine release of colon cancer cells after treatment with crocin, as well as to investigate the signaling pathway that is regulated by crocin. The inhibition rates of different doses of crocin on the proliferation of HCT116 cells were measured by MTT assay. The IC 50 was calculated from the inhibition rates at 48 h. Proliferation curves of HCT116 cells were plotted after treatment with 271.18 µM (high-dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
3
6
0
Order By: Relevance
“…The significant changes compared with vehicle-treated (0 mg/kg of crocin) mice marked as^p value. (Wang et al, 2020) and 3 mM (24 h IC 50 ) in CT-26 cells (Amerizadeh et al, 2018). In SW480 cells, our data is consistent with previous research (Li et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The significant changes compared with vehicle-treated (0 mg/kg of crocin) mice marked as^p value. (Wang et al, 2020) and 3 mM (24 h IC 50 ) in CT-26 cells (Amerizadeh et al, 2018). In SW480 cells, our data is consistent with previous research (Li et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…This study has some limitations. According to previous studies, crocin reduced the cell viability at different concentrations in different cells, such as 271.18 μM (48 h IC 50 ) in HCT116 cells ( Wang et al, 2020 ) and 3 mM (24 h IC 50 ) in CT-26 cells ( Amerizadeh et al, 2018 ). In SW480 cells, our data is consistent with previous research ( Li et al, 2012 ).…”
Section: Discussionmentioning
confidence: 87%
“…On treatment with safranal and crocin, the cells exhibited a dose-dependent cell viability inhibition pattern, similar to saffron (Figures 3 and 4). Safranal and crocin dose ranges in our study are close to the effective doses published for other cancers [9,18,19]. Malaekeh-Nikouei et al have reported safranal's effective dose range to be much higher for other cells suggesting that HCT116 cells have a higher susceptibility [20].…”
Section: Discussionsupporting
confidence: 86%
“…The results of crocin treatment are also consistent with the previous findings where the crocin treatment has inhibited invasion of different cell lines including HUVEC (human umbilical vein endothelial cells), AGS and HGS-27 (gastric cancer cells), and MG63 (osteosarcoma) [22,23]. Interestingly, Wang et al reported crocin's inability to inhibit the invasion of HCT116 cells, at 271.18 µM, but comparing it with the present findings suggests that a higher dose is required to inhibit invasiveness (Figure 5) [19]. In patients with CRC, recurrence and metastasis are the most common causes of cancer-related death.…”
Section: Discussionsupporting
confidence: 77%
“…Previous research suggested that crocin promoted the phosphorylation of STAT3 in the colon cancer cells. [ 39,40 ] Previous studies have revealed a similar pattern of inhibition of breast cancer cells in Riccardin D induced apoptosis. [ 41 ] Altogether, these results suggested that following NF‐κB inhibition, crocin may induce apoptosis via modulating the MAPK‐regulated apoptotic signaling pathway.…”
Section: Discussionmentioning
confidence: 84%